COFFEE GROUND ACTIVATED CHARCOAL AND ITS POTENTIAL AS AN ADSORBENT OF Ca2+ AND Mg2+ IONS IN REDUCING WATER HARDNESS - Achmad Khaerul Mustaqim; Sutanto Sutanto; Yulian Syahputri (Helium: Journal of Science and Applied Chemistry, 2021)
Residents of Ciaruteun Udik Village experienced complaints about the well water they use, namely the presence of scale on cooking utensils, soap is difficult to foam, and indigestion due to consuming hard water. One way to reduce water hardness is by adsorption. Coffee grounds can be used as activated charcoal and function as an adsorbent for calcium and magnesium metal ions. The purpose of this study was to determine the optimum contact time, pH, and weight of coffee grounds in the maximum adsorption of hardness in water. This study begins with the preparation of samples in hard water and coffee grounds, namely by activation with HCl, then the FTIR test of coffee grounds before and after activation. Activated coffee grounds charcoal was tested for adsorption capacity against hardness in water with variations in contact time, pH, and weight of the adsorbent. The results showed that coffee grounds activated charcoal can be used as an adsorbent in reducing water hardness. The optimum pH and contact time of coffee grounds activated charcoal in adsorption of hardness in water was at a contact time of 75 minutes and pH 7 with a hardness level in water of 565.17 mg CaCO3/L decreasing to 56 mg CaCO3/L. The optimum weight of coffee grounds activated charcoal in adsorption of hardness in water was 10 grams with hardness levels in water from 565.17 mg CaCO3/L decreasing to 12 mg CaCO3/L.